Deep Plane Facelift: An Evaluation of the High-SMAS versus Standard Incision Points - Sand, Jordan P.; Amodeo, Chiara Andretto; Nabili, Vishad; Keller, Gregory S. (Facial Plastic Surgery, 2018)
In surgery of the aging face, operative adjustments of the superficial musculoaponeurotic system (SMAS) enhance facial contours. The senior author has observed that the standard deep plane face lift entry points on the SMAS do not provide as much tissue movement in a vertical direction as high-SMAS deep plane face lift entry points. In this study, tissue movement was measured comparing the conventional SMAS entry point with a high-SMAS entry point for deep plane face lifts. Institutional review board approval was obtained. Fourteen facelift patients were enrolled, 10 female and 4 male. Average age was 63.4 (50–81) years. Tissue movement at three points along the jaw line was measured intraoperatively. Standard SMAS entry point suspension resulted in average vertical movements of 6.4, 10.3, and 13.8 mm and average horizontal movements of 3.5, 5.7, and 6.5 mm. High-SMAS entry point resulted in average vertical movements of 11.8, 17.9, and 24.1 mm and average horizontal movements of 5.8, 9.8, and 9.9 mm. This resulted in a 77.3% increase (p = 0.03) in vertical movement and a 61.4% increase (p = 0.02) in horizontal movement with a high-SMAS entry compared with standard SMAS entry. The high-SMAS entry point for a deep plane facelift resulted in a significant increase in lift for both the horizontal and vertical vector on the facial skin flap when compared with the conventional entry.
Keywords: facelift; aging face; high-SMAS